Universitäre Industriekooperation, Informationszugang und Freiheit der Wissenschaft Eine Fallstudie - Gärditz, Klaus Ferdinand (Mohr Siebeck, 2019)
Klaus Ferdinand Gärditz's case study sets out the legal framework for collaborations between universities and private sponsors, where the responsibility to protect academic freedom requires particular safeguarding in order to ensure that authoritative, independent, and credible research can be carried out by public universities.